Towards a ("thick", "thin", or "parallel") European society? Understanding the dynamics of European multiplicity. Issue 1 (2nd January 2016) - Buhari-Gulmez, Didem; Rumford, Chris
Abstract : In order to deal with the question of European society, it is useful to introduce a social-theoretical perspective that investigates the dynamics of multiplicity underlying European transformations. There are at least three co-existing routes to Europe-making that often clash with each other: "thick", "thin", and "parallel" Europe-making. These are in tune with definitions of Europe as an "exclusive civilizational entity", as a "problem-solving instrument", and as representing world society, respectively. Based on a notion of European multiplicity, this study argues that contemporary European society cannot to be reduced to a particular dynamic or to a set of actors, norms, and institutions because it paradoxically incorporates at the same time "thick", "thin", and "parallel" Europe-making.